Give up tomorrow [videorecording (DVD)] - Larrañaga, Paco; Collins, Michael (First Run Features, 2012)
Examines the investigation of Paco Larrañaga, a young man sentenced to death for the rape and murder of two sisters on the island of Cebu in the Philippines. Reveals information suggesting that Larrañaga had been framed as the result of a conspiracy involving police and public officials.